Electrochemical Synthesis of Silver Nanoparticles and their Potential Use as Antimicrobial Agent: a Case Study on Escherichia Coli (2012)
ABSTRACT: Silver nanoparticles (AgNP) were synthesized by electrochemical method using high purity metallic silver in the presence of the surfactant Pluronic® f127. The synthesized nanoparticles were characterized using UV-Vis spectroscopy, Dynamic Light Scattering (DLS), X-Ray Dispersion Spectroscopy (XDS) and Scanning Electron Microscopy (SEM). The antimicrobial activity of AgNP was evaluated against Escherichia Coli. In presence of surfactant, the prepared nanoparticles led to a monomodal distribution with an average size less than 100 nm. The minimal inhibitory concentration (MIC) of the resulting suspension was evaluated using micro dilution method and the MIC results are satisfactory.